Relationship between Family Structure with Adolescent Datement Behavior of Young Women - Ariskah, Firda; Irwina Angelia Silvanasari; Zidni Nuris Yuhbaba (LPPM Universitas dr. Soebandi, 2024)
Introduction: The dating behavior of teenagers in Indonesia is quite worrying and leads to risky behavior. The purpose of this study was to determine the relationship between family structure and dating behavior of young women. Methods: This research method uses quantitative research with cross sectional design. The population in this study were 226 young women obtained from the results of the Slovin formula and a sample of 144 respondents, the sample technique used wasSimple random sampling.The independent variable in this study is family structure and the dependent variable is the dating behavior of young women. Collecting data using a questionnaire about the characteristics of respondents, dating behavior practices, and family structure. Results: Most of the family structures of young women are in poor family structures, while most of the courtship behavior in young women is in risky courting. The results of the analysis with Fisher's test obtained a p-value of 0.028 < α 0.05 so that it can be concluded that there isrelationship between family structure and dating behavior of young women. Conclusions: The less good the family structure is, the more risky dating behavior is, the better the family structure, the less risky dating behavior is. Teenagers should be able to avoid risky dating behavior. Families should provide health education about healthy dating and provide supervision. Family nurses should be able to provide sexuality health education to adolescent families.